Upaya DPPKBP3A Dalam Pencegahan Kekerasan Terhadap Perempuan - Fasya, Zahra Nur'aini; Amalia, Nisa Ayu; Az-Zahra, Dyanita Fatimah; Aulia, Dinda Tasya (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2024)
Cases of violence against women in Indonesia still show quite high numbers, especially in the City of Tasikmalaya, namely 73 cases. These cases are only a handful of the many cases of violence against women because in fact there are still many victims of violence against women who do not report them to the authorities or the services. Researchers formulated the objectives of this study, namely to find out the efforts of DPPKBP3A in preventing violence against women in Tasikmalaya City. Researchers used a descriptive qualitative approach as a method in this study with case studies as the type of research used. Researchers formulate the results of this study showing that violence against women occurs in the household, bullying, and sexual violence. Efforts to prevent violence against women can be done by carrying out outreach to the community. Community outreach is carried out in order to increase public knowledge about how to prevent and deal with violence and harassment against women and children